EFFECT OF THINNING ON GROWTH OF DIFFERENT AGES OF Eucalyptus camaldulensis Dehnh. PLANTATION - Jamroenprucksa, Monton (วารสารวนศาสตร์ไทย, 2022)
The role of thinning in Thailand's forest village plantations, Somdet, Kalasin province, was assessed Specifically, the study sought to investigate the post-thinning situation in 4-year old and 7-year-old Eucalyptus camaldulensis plantations, particularly the response of the tree stands. In this case, tree stands with an initial spacing of 2 m x 8 m were thinned to three spacing levels 4 m x 8 m, 2 m x 16 m, and 8 m x 8 m. Application of thinning affected tree growth. Based on the growth parameters: relative growth rate (RGR), net assimilation rate (NAR), leaf area index (LAI) and crop growth rate (CGR), thinning of stands with an original spacing of 2 m x 8 m (S0) to 4 m x 8 m (S1), 2 m x 16 m (S2) and 8 m x 8 m (S3) showed better growth in both the 4-year-old and the 7-year-old plantation. However, trees in the 7-year-old plantation were found to be more sensitive to thinning than those in the 4-year-old plantation. The trees in the 4 year old plantation showed significant difference only between the highly thinned stand (S3) and the unthinned stand (S0), but trees in the 7 year old plantation showed significant differences between the thinned group (S1,. S2, S3) and the unthinned stand (S0). The study recommends that thinning should not be applied in 4-year-old plantation if the purpose is just to enhance growth of tree stands, but it was shown to be essential in 7-year-old plantation.